New techniques for breeding maize (Zea mays) varieties with fall armyworm resistance and market-preferred traits for sub-Saharan Africa - Matova, Prince M.; Kamutando, Casper N.; Warburton, Marilyn L.; Williams, W. Paul; Magorokosho, Cosmos; Shimelis, Hussein; Labuschagne, Maryke T.; Day, Roger; Gowda, Manje (Wiley, 2023)
Deploying maize varieties with fall armyworm (Spodoptera frugiperda [J.E. Smith]; FAW) resistance, desirable product profiles (PPs) and climate resilience is fundamental for food and economic security in sub-Saharan Africa (SSA). This study reviewed and identified challenges and opportunities for effective and accelerated breeding of demand-led maize hybrids with FAW resistance and adaptation to the diverse agro-ecologies of SSA. Lessons were drawn on improving breeding efficiency through adequate genetic variation delivered via prebreeding programmes, speed breeding and a reduced breeding stage plan. Appropriate PPs aligned with demand-led breeding approaches were highlighted as foundations for variety design and commercialization. Challenges to accelerated FAW resistance breeding in maize included inadequate funds and modern tools; poor adaptation of some exotic donor parental lines; lack of information on FAW resistance among local varieties; lack of integration of molecular markers associated with FAW resistance and agronomic traits into selection plans; and limited infrastructure for FAW rearing and germplasm screening. Integration of modern breeding tools and scientific innovations were recommended for accelerated development and release of FAW resistant and market-preferred maize varieties.